2021
DOI: 10.3389/fmolb.2021.711710
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sonic Hedgehog Pathway in the Development of the Central Nervous System and Aging-Related Neurodegenerative Diseases

Abstract: The Sonic hedgehog (SHH) pathway affects neurogenesis and neural patterning during the development of the central nervous system. Dysregulation of the SHH pathway in the brain contributes to aging-related neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis. At present, the SHH signaling pathway can be divided into the canonical signaling pathway and non-canonical signaling pathway, which directly or indirectly mediates other related pathways involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…TBIs result in a wide breadth of pathologies, with excitotoxicity contributing to many TBI-induced sequelae [ 43 ]. Previously, Shh signaling was reported to reduce excitotoxicity following middle cerebral artery occlusion in rodents [ 45 , 46 ], though it was never examined following TBI in adult zebrafish. To test if Shh signaling could affect glutamate-induced excitotoxicity, undamaged fish were either left untreated, treated with the Smo agonist purmorphamine, which is a Shh signaling activator, or treated with both purmorphamine and cyclopamine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TBIs result in a wide breadth of pathologies, with excitotoxicity contributing to many TBI-induced sequelae [ 43 ]. Previously, Shh signaling was reported to reduce excitotoxicity following middle cerebral artery occlusion in rodents [ 45 , 46 ], though it was never examined following TBI in adult zebrafish. To test if Shh signaling could affect glutamate-induced excitotoxicity, undamaged fish were either left untreated, treated with the Smo agonist purmorphamine, which is a Shh signaling activator, or treated with both purmorphamine and cyclopamine.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the results of Shh signaling activators have been inconsistent. For example, in epileptic rodents, Feng et al [ 70 ] reported that increased Shh expression exacerbated seizure activity and negatively regulated extracellular glutamate, while others reported data suggesting that Shh activity upregulated EAAT2 expression, reduced astrocyte reactivity, and combated excitotoxicity [ 45 , 46 , 71 , 72 ]. Other studies reported that Shh activation is neuroprotective [ 23 , 37 , 38 , 39 ] and is effective in regenerative therapies [ 35 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hedgehog signaling pathway: The Sonic hedgehog (SHH) signaling pathway is involved in neurogenesis, neural patterning and cell survival during nervous system development [ 66 , 67 ]. SHH signaling requires intact primary cilia in brain cells and fails with structurally disrupted cilia.…”
Section: Discussionmentioning
confidence: 99%
“…A potential role of such an established developmental pathway in age-related neurodegeneration is emerging. Dysregulation of the Shh pathway has been reported in neurodegenerative diseases such as Alzheimer's disease 47,58,59 , Parkinson's disease 60,61 , Huntington's disease 62 and ALS [63][64][65] , demonstrating the importance of fully functioning Shh pathway, not only during development, but also during ageing. While further research is needed, we provide evidence that this dysfunction of this overlooked organelle is a contributing factor to the complex pathobiology in ALS.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the key pathway components localize within the organelle or have been otherwise associated with the ciliary function [42][43][44] . Shh signaling is involved in multiple developmental and several adult homeostatic processes [45][46][47] . Consequently, precise regulation is required via controlled intraflagellar transport (IFT) of positive (SMO) or negative (GPR161; SUFU) regulators inside or out of the cilium 38,39,43,44,48,49 .…”
Section: Shh Signaling Is Perturbed Upon C21orf2 Knockdownmentioning
confidence: 99%